Pemberian PMT Susu dan Telur pada Anak dengan Resiko Stunting di Wilayah Kerja Puskesmas Tembilahan Hulu Kabupaten Indragiri Hilir Provinsi Riau - Susi Ernawati; Siti Maimunah; Fatya Nurul Hanifah (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
The consumption of animal protein sources is highly crucial for nutritional intake during the developmental period, particularly in the first 1000 days of life. By consuming animal protein sources during this critical period, it can enhance growth, cognitive function, and the nutritional status of children. The long-term effect of consuming protein-rich foods is to improve the nutritional status of toddlers. The objective of this community service is to increase awareness regarding the provision of supplemental foods such as eggs and milk to children at risk of stunting. This is done by providing education on supplemental foods to children within the Puskesmas Tembilahan Hulu area. The outcome of the community service is the improved knowledge of mothers and the provision of eggs and milk to participants' toddlers at risk of stunting within the working area of Puskesmas Tembilahan Hulu, totaling 10 children.